2023
DOI: 10.3390/s23010501
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Diagnostic and Physiotherapy Approach for a Patient with Parsonage–Turner Syndrome—A Case Report

Abstract: Parsonage–Turner syndrome (PTS) is a rare neurological disorder that causes major diagnostic problems. This paper presents a case report of a patient with PTS and proposes a new physiotherapy program. Case description: a 23-year-old man presents a sudden severe pain of his right arm. The man is consulted by several doctors and physiotherapists. Three magnetic resonance imagings (MRI), a nerve conduction study (NCS), and needle electromyography (EMG) are performed. After 6 months, based on medical history, phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Given that this is the first reported case to utilize an ESI for the treatment of brachial neuritis and the injection was given prior to the emergence of any chronic sequelae, further investigation will be needed for a more definitive answer to the relationship between ESI and rehabilitation in the healing of brachial neuritis. Physiotherapy does appear to be of benefit in the rehabilitation of brachial neuritis [ 20 ]; however, further studies would be needed to draw a more significant conclusion. Due to its benefits, we would recommend it regardless.…”
Section: Discussionmentioning
confidence: 99%
“…Given that this is the first reported case to utilize an ESI for the treatment of brachial neuritis and the injection was given prior to the emergence of any chronic sequelae, further investigation will be needed for a more definitive answer to the relationship between ESI and rehabilitation in the healing of brachial neuritis. Physiotherapy does appear to be of benefit in the rehabilitation of brachial neuritis [ 20 ]; however, further studies would be needed to draw a more significant conclusion. Due to its benefits, we would recommend it regardless.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristic element of this case report was the proposed rehabilitation treatment; the multimodal approach, related to timing and short-, medium-, and long-term goals, appears to have contributed to the recovery of strength and function of the upper limb. Currently, in the literature, the rehabilitation process lacks certainty, but some elements seem effective and are widely used, such as neurodynamic techniques [ 20 ]. Recent studies have shown that a multidisciplinary approach appears valid in managing these patients, emphasizing the importance of sensorimotor recovery, including exercises for regaining upper limb proprioceptive abilities and motor imagery [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The selection of an appropriate rehabilitation technique should therefore refer directly to the registered functional changes in nerves The available literature databases do not provide clear and comprehensive data on the algorithms of rehabilitation procedures in patients with brachial plexus injuries, similar to those presented in our study, developed especially using the results of neurophysiological tests. Few scientific reports correlated the results of neurophysiological tests with imaging tests or selected rehabilitation procedures, but they did not concern the starting base for further therapeutic procedures [49][50][51]. An extensive review by Li et al [52] shows that a clear rehabilitation process has not been developed yet.…”
Section: Discussionmentioning
confidence: 99%